Gunshot Wound: Pathogenesis - Makarov, Vitaliy; Pavlov, Sergey; Shevchenko, Rostislav; Feskov, Volodymyr; Kumetchko, Marina; Petiunin, Oleksii; Myroshnychenko, Dmytro; Babenko, Nataliia; Litvinova, Olga (Scripta Medica, 2026)
Gunshot wounds remain one of the most complex types of combat injuries. A gunshot wound is a dynamic system in which the initial mechanical destruction of tissue is only the starting point of a complex and multi-level process. Subsequently, the wound site steadily transforms and the volume of non-viable tissue increases, spreading beyond the wound channel area. This review examines the pathogenesis of a gunshot wound, which is a chain of cause-and-effect changes in which each link is formed as a direct consequence of previous disturbances. The pathophysiological events that contribute to the chronic wound process are identified, which cannot be interrupted by natural mechanisms.